Prevention versus Clinical Management of Suicide Attempts in Adolescents: What are the Costs? (2018)
Introduction: Suicide is a worldwide public health problem, and being the youth are among one of the most affected population groups. In Colombia there is no evidence available about the cost of suicide care or prevention. Or attention to those who make suicide attempts assistance or prevention of suicide. This type of analysis is necessary to guide decisions about resource distribution in mental health and to reduce suicideal rates amongst youths in our country. Thus, the purpose of this study is to estimate and compare the mean cost of in-patient care cost treatment cost of youth suicidal youth suicide attempts, with the mean cost of participation in a school-based suicide preventive prevention program in for adolescents. Materials and methods: Medical charts of adolescents hospitalized for suicideal attempts were reviewed, along with as well as registries from adolescent participants in a suicide preventive program in Bogotá in 2010. Resources used were identified and tariff costs were quantified. Results: The average in-patients cost of a teenage suicideal attempt was {dollar}1 814 000 Colombian pesos (cop) (n = 39) Colombian pesos, and of {dollar}10 307 000 cop (n = 5) Colombian pesos when intensive care was required. The average cost of participation in a prevention ve program was {dollar}113 000 cop (n = 24) Colombian pesos per high-risk teenager and of {dollar}47 000 cop (n = 101) Colombian pesos for teenagers without suicide such risk. Conclusion: With For the average in- patient cost of one suicidal suicide attempt, 16 high-risk teenagers could be enrolled in a suicide preventive prevention program.